Polyethylene glycol succinate as well as preparation method and application thereof
Patent Information
- Application Number
- CN202510258104.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-06
AI Technical Summary
Polyethylene succinate is prone to molecular chain breakage and degradation in high temperature environments, resulting in deterioration of material properties, and its mechanical strength, barrier properties and degradation properties are insufficient, making it difficult to meet the application needs of high mechanical properties and environmental protection requirements.
By adding organic montmorillonite, glass fiber and nanosilicon dioxide to the preparation method of polyethylene succinate, the thermal stability, mechanical properties, barrier properties and degradation properties of the material are improved, and a highly active catalyst is used to speed up the reaction and reduce by-products.
It significantly improves the thermal stability, mechanical properties and degradation properties of polyethylene succinate, imparts durability and environmental protection performance in complex environments, and is suitable for applications such as water quality monitoring floats.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyethylene succinate production, in particular to polyethylene succinate and a preparation method and application thereof. Background Art
[0002] As a biodegradable polyester material, polyethylene succinate (PES) has received widespread attention in many fields in recent years. However, it has some performance limitations, which restrict its application in some specific scenarios. The thermal decomposition temperature of pure polyethylene succinate is relatively low. Under high temperature conditions, the molecular chain is prone to breakage and degradation, resulting in degradation of material properties. In terms of mechanical strength, its tensile strength, bending strength and impact toughness are limited. This makes it easy for products made based on it to deform, rupture and other problems when subjected to large external forces, making it difficult to meet the application requirements with high mechanical properties. And its barrier effect on gases and liquids is not ideal.
[0003] Due to the above performance defects, when polyethylene succinate is used in the field of water quality monitoring buoys, the problem is further magnified. Water quality monitoring buoys are exposed to complex outdoor natural environments for a long time and have to withstand high temperatures, strong ultraviolet radiation, wind and wave impacts, and collisions with various objects in the water.
[0004] In addition, although traditional water quality monitoring buoys often use polyolefin plastic materials such as polyethylene (PE) and polypropylene (PP), they have certain advantages, but they also have problems such as poor thermal stability, insufficient mechanical strength, poor barrier properties, and difficulty in degradation, resulting in microplastic pollution. Although poly(ethylene succinate) has the advantage of being degradable, the above performance shortcomings make it unable to fully meet actual needs when used as a water quality monitoring buoy material.
[0005] In summary, there are many problems with both the performance of polyethylene succinate itself and the traditional water quality monitoring buoy materials, which urgently need to be solved through new material formulations and preparation processes to improve the performance of water quality monitoring buoys, ensure the efficient implementation of water quality monitoring work, and reduce pollution to the water environment. Summary of the invention
[0006] In view of the above shortcomings in the prior art, the purpose of the present invention is to provide a polyethylene glycol succinate, which accelerates the reaction and reduces the generation of by-products by improving the catalytic activity. At the same time, it has a stable structure, a firm load, good reusability, and can reduce production costs.
[0007] Another object of the present invention is to provide a method for preparing polyethylene succinate, by adding organic montmorillonite, glass fiber and nano-silica, etc., to improve the thermal stability, mechanical properties, barrier properties and degradation properties of polyethylene succinate.
[0008] The third object of the present invention is to provide an application of polyethylene succinate. The water quality monitoring buoy prepared with polyethylene succinate as the main material has a strong ability to adapt to complex outdoor environments, is environmentally friendly and durable, and also has antibacterial and good electrical properties to ensure the normal operation of the monitoring equipment.
[0009] The present invention is achieved by adopting the following technical solutions: The preparation method of poly(ethylene succinate) comprises the following steps: (1) Add succinic acid and ethylene glycol to a reactor, add a catalyst accounting for 0.1-0.5% of the total mass of the raw materials, control the reaction temperature at 160-180°C, the pressure at 0.1-0.3 MPa, the stirring speed at 100-300 rpm, react for 2-4 hours, and esterification reaction occurs to generate oligomers containing terminal carboxyl groups and terminal hydroxyl groups; then reduce the temperature to 120-150°C, add nano-silica sol in batches under stirring conditions, increase the stirring speed to 300-500 rpm, and stir for 1-2 hours; (2) After the treatment in step (1) is completed, the reaction temperature is increased to 220-260°C, and the reaction system is evacuated to a vacuum with a pressure lower than 100 Pa. At the beginning of the polycondensation reaction, the organic montmorillonite is dispersed in toluene to form a suspension, which is added to the reaction system to continue the polycondensation reaction for 3-8 hours; (3) After the polycondensation reaction is completed, the product is taken out from the reactor and cooled to room temperature. The cooled product is blended and extruded with short-cut glass fibers in a twin-screw extruder to obtain polyethylene succinate.
[0010] The molar ratio of succinic acid to ethylene glycol is 1:(1.2-1.5); the addition amount of organic montmorillonite is 2-5% of the theoretical output mass of polyethylene succinate; the addition amount of glass fiber is 10-25% of the theoretical output mass of polyethylene succinate; and the addition amount of nano-silicon dioxide is 3-8% of the theoretical output mass of polyethylene succinate.
[0011] The nano-silica sol must be pretreated before being added. The pretreatment process is: disperse the nano-silica in anhydrous ethanol, add a silane coupling agent, and stir at 70-80°C for 2-3 hours to graft organic groups on the surface of the nano-silica to form a stable sol; the chopped glass fiber must be pretreated before being added. The pretreatment process is: soak the chopped glass fiber in a solution of vinyl trimethoxysilane, take it out after 1-2 hours, and dry it. The silane coupling agent is γ-aminopropyl triethoxysilane (KH-550).
[0012] The pretreatment process of organic montmorillonite is as follows: dispersing montmorillonite in toluene, stirring and reacting at 80-100°C for 2-3h to allow the organic modifier to be inserted into the interlayer of montmorillonite, and then filtering, washing, drying and other steps to obtain the organic montmorillonite; dispersing the organic montmorillonite in the inert solvent toluene, and ultrasonically treating the montmorillonite suspension (20-40kHz, 30min) before adding it to the reaction system; and vacuum extracting after adding it to the reaction system to ensure that the solvent residue does not affect the polycondensation reaction.
[0013] Processing process of nano-silica sol: Select nano-silica powder with a particle size of 20-50nm and a purity of not less than 99%, prepare γ-aminopropyltriethoxysilane (KH-550), and anhydrous ethanol (water content less than 0.1%) to avoid interference of water on the reaction. Slowly add nano-silica powder to anhydrous ethanol, and the mass ratio of nano-silica to anhydrous ethanol is controlled at 1: (10-20). During the addition process, use a high-speed stirrer for stirring, set the stirring speed to 800-1200 rpm, and continue stirring for 30-60 minutes to make the nano-silica initially dispersed in ethanol to form a uniform suspension. Weigh KH-550 according to 3-5% of the mass of nano-silica. Slowly add it to the above-mentioned nano-silica suspension, keep stirring during the addition process, and control the drop rate to 3-5 drops per min. After the addition is completed, continue stirring for 30 minutes to ensure that the coupling agent is evenly dispersed in the system. The reaction temperature is raised to 70-80°C, and the reaction is carried out at this temperature for 2-3 hours. Stirring is continued during the reaction, and the stirring speed is adjusted to 400-600 rpm, so that KH-550 and nano-silica react fully and organic groups are grafted onto the surface of nano-silica. After the reaction is completed, the reaction system is cooled to room temperature. Then, an ultrasonic disperser is used to ultrasonically treat the reacted sol, and the ultrasonic power is set to 300-500W and the ultrasonic time is 15-20min. Ultrasonic treatment further refines the dispersion state of the nano-silica particles, improves the stability of the sol, and finally forms a stable nano-silica sol.
[0014] Processing process of chopped glass fiber: Select vinyl trimethoxysilane, use anhydrous ethanol as solvent, prepare a dilute coupling agent solution with a mass fraction of 2-5%. During the preparation process, stir it fully to ensure that the coupling agent is completely dissolved in ethanol. Soak the chopped glass fiber (length 3-6mm) in the prepared dilute coupling agent solution to ensure that the glass fiber is completely immersed in the solution. The soaking time is controlled at 1-2h, so that the coupling agent molecules have enough time to react chemically with the surface of the glass fiber. After the soaking is completed, take the chopped glass fiber out of the coupling agent solution and gently absorb the excess solution on the surface with filter paper. Then, put the glass fiber into an oven for drying, the drying temperature is set to 80-100℃, and the drying time is 2-3h. Through the drying treatment, the solvent on the surface of the glass fiber is removed, and the coupling agent forms a stable chemical bond on the surface of the glass fiber, so that the active group that can be well combined with polyethylene succinate is formed on the surface of the glass fiber.
[0015] Organic montmorillonite has a layered structure and can form a good interface with the polyethylene glycol succinate matrix, playing a role in strengthening and toughening; glass fiber is used as a reinforcing material and is evenly dispersed in the matrix, greatly improving the tensile strength, bending strength and other mechanical properties of the material. Nano-silicon dioxide is filled inside the material to improve the microstructure and further enhance the overall strength of the material. The addition of organic montmorillonite and nano-silicon dioxide improves the thermal stability of the material. They can form a barrier layer when the material is heated, delay heat transfer, inhibit thermal degradation of the polymer matrix, and enable polyethylene glycol succinate to maintain better performance in high temperature environments. The lamellar structure of organic montmorillonite and the nano-size effect of nano-silicon dioxide form a tortuous path inside the material, hindering the diffusion of gas and liquid molecules, thereby improving the barrier properties of polyethylene glycol succinate, making it perform better in terms of waterproofing and gas penetration.
[0016] The method for preparing the catalyst comprises the following steps: a. Add mesoporous silica to an anhydrous ethanol solution containing a silane coupling agent, the amount of the silane coupling agent being 1-3% of the mass of the mesoporous silica, and stir the reaction at 60-80°C for 2-4h; b. In a dry glove box, tetrabutyl titanate was added to anhydrous ethanol to prepare a 0.1 mol / L tetrabutyl titanate ethanol solution; lanthanum acetate was added to anhydrous ethanol to prepare a 0.05 mol / L lanthanum acetate ethanol solution; zinc oxide nanoparticles and boric acid were taken, added to anhydrous ethanol, and ultrasonically dispersed for 30-60 min; c. The prepared tetrabutyl titanate ethanol solution and lanthanum acetate ethanol solution were mixed in a molar ratio of titanium: lanthanum = 3:1, and stirred continuously during the mixing process, and polyvinyl pyrrolidone was added as a dispersant, and stirred for 1-2h to obtain a main catalyst solution; then the mixed solution containing zinc oxide nanoparticles and boric acid was added to the main catalyst solution, and stirring was continued for 30-60min; d. The mesoporous silica obtained in step a is added to the solution obtained in step c, so that the catalyst is loaded in the pores of the mesoporous silica, stirred at room temperature for 2-4 hours, and then heated and stirred at 60-80°C for 4-8 hours; e. The product obtained in step d is filtered and washed, then transferred to a vacuum drying oven and dried at 60-80°C for 12-24h; after drying, it is placed in a muffle furnace and calcined at 250-300°C for 2-3h while nitrogen is introduced for protection, and an activation treatment is performed to remove organic matter and impurities on the surface to obtain a catalyst; the catalyst specific surface area BET ≥ 200m² / g.
[0017] The amount of the silane coupling agent is 1-3% of the mass of the mesoporous silica, the amount of the zinc oxide nanoparticles is 5-10% of the total mass of the main catalyst, the amount of boric acid is 2-5% of the total mass of the main catalyst; the amount of polyvinyl pyrrolidone is 0.5-1% of the mass of the tetrabutyl titanate ethanol solution; the loading amount of the catalyst is 20-40%. The silane coupling agent is γ-aminopropyltriethoxysilane (KH-550). The loading amount is the percentage of the total mass of the active components to the mass of the mesoporous silica carrier.
[0018] The combination of tetrabutyl titanate and lanthanum acetate brings out the synergistic effect of the two catalysts, provides more active sites, accelerates the esterification and polycondensation reaction rates, shortens the reaction time, and improves production efficiency. The addition of zinc oxide nanoparticles and boric acid as co-catalysts stabilizes the active structure of the catalyst, maintains a high catalytic activity during the reaction, reduces the loss and deactivation of active components, and ensures stable reaction. Mesoporous silica, as a carrier, has a high specific surface area and rich pore structure, can effectively load active components, prevent them from agglomerating, and improve the stability and reusability of the catalyst. At the same time, by controlling the loading amount and calcination conditions, the structure of the catalyst is optimized and its catalytic performance is guaranteed.
[0019] The poly(ethylene glycol succinate) is prepared by the above method for preparing poly(ethylene glycol succinate).
[0020] The poly(ethylene glycol succinate) is used to prepare a water quality monitoring buoy.
[0021] The method for preparing the water quality monitoring buoy comprises the following steps: Ⅰ. In a high-speed mixer, first add polyethylene succinate particles, then add hindered amine light stabilizer, maleic anhydride grafted polyethylene succinate in sequence, and stir at 50-80°C for 5-10 minutes; then add nano-silver antibacterial agent, continue stirring, then add nano-calcium carbonate and graphene dispersion, and continue stirring for 10-20 minutes; Ⅱ. Add the material obtained in step Ⅰ into a twin-screw extruder for melt blending and extrusion. At the same time, during the extrusion process, add the carbon nanotube suspension into the twin-screw extruder and mix it with other materials. Control the screw speed at 100-300 rpm. Then extrude it into the shape of a water quality monitoring buoy through a mold, and then cool it by air cooling or water cooling to obtain a water quality monitoring buoy.
[0022] The mass parts of the raw materials are as follows: polyethylene succinate: 100 parts; carbon nanotubes: 1-3 parts; hindered amine light stabilizer: 0.5-2 parts; nano silver antibacterial agent: 0.3-1 parts; graphene: 0.5-2 parts; maleic anhydride grafted polyethylene succinate: 5-15 parts; nano calcium carbonate: 5-15 parts.
[0023] The preparation method of the carbon nanotube suspension is as follows: placing the carbon nanotubes in a mixed acid solution of concentrated nitric acid and concentrated sulfuric acid, and reflux treatment at 60-80°C for 2-4h; washing with deionized water until neutral, and drying to obtain purified carboxylated carbon nanotubes; dissolving polyvinyl alcohol (PVA) in deionized water to prepare a solution with a mass fraction of 1-5%; adding the purified carbon nanotubes to the PVA solution, and ultrasonically treating (power 200-500W, time 30-60min) to make PVA uniformly coated on the surface of the carbon nanotubes; centrifugation and drying to obtain PVA-coated carbon nanotubes; adding the dried PVA-coated carbon nanotubes to N,N-dimethylformamide (DMF), and ultrasonically dispersing or mechanically stirring (speed 1000-2000 rpm, time 1-2h) to form a uniform suspension. The preparation method of nano calcium carbonate dispersion is: surface modification of nano calcium carbonate is carried out with fatty acid and titanate coupling agent, silane coupling agent is added at the same time, and the surface is organicized at 80-120°C for 1-2 hours, and the nano calcium carbonate is co-modified by a combination of titanate coupling agent + silane coupling agent to enhance the surface hydrophobicity; the preparation method of graphene dispersion is: graphene is made into a uniform dispersion in an organic solvent or water by ultrasonic stripping. The amount of silane coupling agent added is 1-5% of the mass of nano calcium carbonate.
[0024] In the raw material system of water quality monitoring buoys, polyethylene succinate is the basic continuous phase matrix. Granular or fibrous raw materials such as nano calcium carbonate, carbon nanotubes, and graphene are dispersed in it, and they are closely combined with polyethylene succinate like fillers. Nano calcium carbonate, with its tiny size and large specific surface area, is evenly filled in the molecular gaps of polyethylene succinate, increasing the density of the material while playing a physical reinforcement effect, improving the hardness and rigidity of the buoy. Carbon nanotubes and graphene, with their unique microstructure, build a three-dimensional network structure in the polyethylene succinate matrix, significantly enhancing the mechanical strength, thermal stability and conductivity of the material. For example, carbon nanotubes can bear part of the external stress with their own excellent mechanical properties, so that the buoy can better maintain structural integrity and is not easily damaged when it is impacted by water flow and hit by wind and waves. Silane coupling agent, maleic anhydride grafted polyethylene succinate (PES-g-MAH) and other substances act as chemical bridges between polyethylene succinate and other raw materials. The siloxy group at one end of the silane coupling agent molecule can react chemically with the hydroxyl group on the surface of inorganic raw materials such as nano-calcium carbonate and nano-silicon dioxide, and the organic functional group at the other end reacts physically or chemically with the polyethylene succinate molecule, thereby enhancing the interfacial bonding force between the inorganic raw materials and polyethylene succinate. The maleic anhydride group in PES-g-MAH can react with active groups such as hydroxyl groups on the surface of organic montmorillonite and glass fiber, and its polyethylene succinate chain segment can be well compatible with the matrix polyethylene succinate, which improves the compatibility of organic montmorillonite, glass fiber and polyethylene succinate matrix, reduces the phase separation phenomenon, and enables each raw material to form a more stable overall structure in the buoy material system. Functional raw materials such as hindered amine light stabilizers and nano-silver antimicrobial agents work synergistically with polyethylene succinate to give the buoy special properties. Hindered amine light stabilizers can effectively absorb ultraviolet rays, inhibit the oxidative degradation reaction of polyethylene succinate under light, and extend the service life of the buoy in outdoor environments. Nano-silver antimicrobial agents can inhibit the growth and reproduction of bacteria, algae and other microorganisms on the surface of the buoy, prevent microbial attachment and corrosion, keep the surface of the buoy clean, and work together with polyethylene succinate to improve the durability and stability of the buoy in complex water environments. In addition, glass fiber enhances the mechanical strength of polyethylene succinate, allowing it to withstand greater external forces, and together with other raw materials, ensures that the buoy works normally under various harsh natural conditions.
[0025] Compared with the prior art, the present invention has the following beneficial effects: (1) The catalyst of the present invention uses mesoporous silica as a carrier, tetrabutyl titanate, lanthanum acetate, etc., zinc oxide nanoparticles and boric acid as catalysts, and γ-aminopropyltriethoxysilane (KH-550) as a silane coupling agent. The components work together to make the catalyst highly active and selective, accelerate the reaction, and reduce by-products. It has good thermal and chemical stability and is stable at high temperatures and in complex environments; it has a strong load and good reusability, which can reduce production costs.
[0026] (2) Organic montmorillonite, glass fiber and nano-silica are added when preparing polyethylene succinate. Organic montmorillonite strengthens and toughens, glass fiber improves mechanical properties, and nano-silica improves microstructure and enhances overall strength. The three work together to improve the thermal stability and barrier properties of the material, and also improve degradation performance, which is conducive to decomposition in the natural environment.
[0027] (3) The water quality monitoring buoy made of polyethylene succinate as the main raw material has excellent comprehensive performance, good thermal stability, and can adapt to high outdoor temperatures; high mechanical strength, can withstand external impact; strong barrier properties, protect monitoring equipment; degradable and water-resistant, environmentally friendly and durable. Adding hindered amine light stabilizers, nano-silver antibacterial agents, etc., gives the buoy anti-ultraviolet and antibacterial properties, extends its service life and keeps its surface clean. In addition, the buoy has good electrical properties, which ensures the stable operation of the monitoring equipment and the smooth progress of water quality monitoring. DETAILED DESCRIPTION
[0028] In order to make the purpose and technical solution of the present invention more clear, the present invention is further described in detail.
[0029] Test method: Catalytic activity test: Succinic acid and ethylene glycol are used as raw materials, and are added to a reaction vessel equipped with a stirring device, a thermometer and a condenser in a molar ratio of 1:1.3. The catalyst to be tested is added (the amount is 0.3% of the total mass of the raw materials), and the esterification reaction is carried out at the set esterification temperature (170°C) and pressure (0.2MPa). The changes in the acid value in the system at different reaction times are recorded (which can be determined by acid-base titration). The faster the acid value decreases, the faster the esterification reaction rate is and the higher the catalytic activity of the catalyst is. After the esterification reaction is completed, the temperature is raised to the polycondensation reaction temperature (240°C), and the vacuum is evacuated to a pressure below 100Pa. The reaction is continued, and the polycondensation reaction process is tracked by measuring the intrinsic viscosity of the system (using an Ubbelohde viscometer). The faster the intrinsic viscosity increases, the faster the polycondensation reaction rate is, which further reflects the activity of the catalyst.
[0030] Selectivity test: The reaction products were analyzed by gas chromatography-mass spectrometry (GC-MS).
[0031] Stability test: Thermal stability: The catalyst was heat treated for 5 hours at a temperature 300°C higher than the actual reaction temperature, and then the reaction was carried out according to the above catalytic activity test method, and the changes in the catalytic activity of the catalyst before and after the heat treatment were compared. The smaller the decrease in activity, the better the thermal stability.
[0032] Chemical stability: Place the catalyst in a simulated reaction system containing raw materials and products, keep it at the reaction temperature for a period of time (24 hours), then take out the catalyst and conduct the catalytic activity test again to observe the activity changes and evaluate its chemical stability.
[0033] Load firmness test: The supported catalyst sample is placed in an ultrasonic cleaner and ultrasonically treated at a certain power (200W) and time (30min). The sample is then centrifuged and the supernatant is taken and the content of active components (such as titanium, lanthanum and other elements) is determined by atomic absorption spectrometry (AAS) or inductively coupled plasma emission spectrometry (ICP-OES) to calculate the shedding rate of the active components. At the same time, the catalyst after ultrasonic treatment is tested again for specific surface area and pore size distribution to observe whether its structure has changed. The lower the shedding rate, the smaller the structural change, indicating that the loading firmness is better.
[0034] Reusability test The first reaction was carried out according to the catalytic activity test method. After the reaction was completed, the catalyst was recovered by filtering, washing, drying and other operations. The recovered catalyst was then put into the same reaction system again for the next reaction, and the process was repeated 5 times. After each reaction, the intrinsic viscosity, conversion rate and other indicators of the product were measured, and the results of each reaction were compared to evaluate the reusability of the catalyst. If these indicators change little with the increase in the number of uses, it indicates that the catalyst has good reusability.
[0035] Thermal stability test method: Initial decomposition temperature (Tonset) and residual mass percentage at 400°C: Thermogravimetric analysis (TGA) is used for testing. Using a thermogravimetric analyzer, place an appropriate amount of sample (8 mg) in a platinum or ceramic crucible, and heat the temperature from room temperature to above the target test temperature (500°C) at a certain heating rate (15°C / min) in an inert gas protection atmosphere such as nitrogen or argon (the gas flow rate is controlled at 50mL / min). During the heating process, the instrument records the change of sample mass with temperature in real time. The initial decomposition temperature (Tonset) refers to the temperature corresponding to the beginning of a significant decrease in the mass of the sample, which reflects the temperature point at which the material begins to thermally decompose. When the temperature reaches 400°C, record the residual mass of the sample at this time and calculate its percentage of the initial mass. The larger the percentage value, the better the thermal stability of the material at 400°C and the lower the degree of decomposition.
[0036] Tensile strength: According to GB / T1040.2, tested using a universal material testing machine.
[0037] Bending strength: According to GB / T9341 standard, use universal material testing machine.
[0038] Izod notched impact strength: According to GB / T1843 standard, the test is carried out using an Izod impact testing machine.
[0039] Barrier Test Methods Oxygen transmission rate: Use an isobaric method or a differential pressure method oxygen transmission rate tester for testing. Taking the isobaric method as an example, the prepared polyethylene succinate film (thickness 0.1mm) is sealed in the middle of the test chamber, and the test chamber is divided into two independent air chambers. Oxygen of known concentration (purity 99.99%) is passed into one air chamber, and inert gas such as nitrogen is passed into the other air chamber. Under certain temperature (25°C) and relative humidity (50%RH), oxygen will diffuse from the high concentration side to the low concentration side through the film. The change of oxygen concentration in the air chamber on the low concentration side is monitored in real time by a sensor, and the oxygen transmission rate is calculated according to the principle and built-in algorithm of the test instrument, with the unit of cm³ / (m²・24h・0.1MPa). The smaller the value, the better the material's barrier performance to oxygen.
[0040] Degradability test method: Mass loss rate after 6 months of soil burial: simulate the natural soil environment for testing. Prepare a certain amount (8g) of polyethylene succinate sample and record its initial mass. Bury the sample in soil that meets certain standards (such as unpolluted garden soil, screened to remove impurities, and ensure uniform soil particles) with a burial depth of 5cm. Allow the sample to degrade in the soil for 6 months under natural environmental conditions (temperature, humidity, etc. close to the local natural climate). After 6 months, carefully take out the sample, rinse it with clean water to remove the soil particles attached to the surface, and then dry it in an oven (temperature of 70°C) to constant weight, and record the sample mass again. According to the formula: mass loss rate = (initial mass - mass after degradation) ÷ initial mass × 100%, calculate the mass loss rate after 6 months of soil burial. The higher the mass loss rate, the better the degradability of the material.
[0041] Shore hardness (Type A): Tested in accordance with GB / T531.1 standard using a Shore A hardness tester.
[0042] Processability test method Processing temperature range: Use a twin-screw extruder to conduct a processing test on polyethylene succinate to determine the processing temperature range. Add polyethylene succinate particles to the hopper of the twin-screw extruder, set the temperature of different areas of the extruder, gradually increase the temperature from a lower temperature, perform extrusion at a certain screw speed (100r / min), and observe the flow state of the material during the extrusion process and the appearance quality of the extrudate (such as whether there are defects such as melt fracture, surface roughness, bubbles, etc.). Record the temperature when obvious processing defects (such as melt fracture, severe surface unevenness, etc.) begin to appear, as well as the temperature range where it can be extruded smoothly and the product quality is good, which is the processing temperature range of the material. When recording, the temperature range where defects of different degrees occur is also marked in detail, such as "175-195 (increased processing defects)" means that the number of defects occurring during the processing process increases within the temperature range of 175-195℃.
[0043] Water resistance test method Water absorption: tested according to GB / T1034 standard.
[0044] Weathering test: GB / T16422.2-2014 "Plastics laboratory light source exposure test method Part 2: Xenon arc lamp".
[0045] Antibacterial performance test: GB / T21510-2008 "Test method for antibacterial properties of nano-inorganic materials".
[0046] Electrical performance test: GB / T1410-2006 "Test method for volume resistivity and surface resistivity of solid insulating materials".
[0047] In the following embodiments, the pretreatment process of the organic montmorillonite, the nano-silica sol and the chopped glass fibers is as follows: The pretreatment process of organic montmorillonite is as follows: montmorillonite is dispersed in toluene, stirred and reacted at 90°C for 3 hours to allow the organic modifier to be inserted into the interlayer of montmorillonite, and then filtered, washed, dried and other steps are performed to obtain the organic montmorillonite; the organic montmorillonite is dispersed in an inert solvent, toluene, and the montmorillonite suspension is ultrasonically treated (30kHz, 30min) before being added to the reaction system; after being added to the reaction system, vacuum extraction is performed to ensure that the solvent residue does not affect the polycondensation reaction.
[0048] Treatment process of nano-silica sol: Select nano-silica powder with a particle size of 30nm and a purity of 99%, prepare γ-aminopropyltriethoxysilane (KH-550), and anhydrous ethanol (water content less than 0.1%) to avoid interference of water on the reaction. Slowly add nano-silica powder to anhydrous ethanol, and the mass ratio of nano-silica to anhydrous ethanol is controlled at 1:15. During the addition process, use a high-speed stirrer for stirring, set the stirring speed to 1000 rpm, and continue stirring for 50 minutes to make the nano-silica initially dispersed in ethanol to form a uniform suspension. Weigh KH-550 according to 4% of the mass of nano-silica. Slowly add it dropwise to the above-mentioned nano-silica suspension, keep stirring during the addition process, and control the drop speed to 4 drops per min. After the addition is completed, continue stirring for 30 minutes to ensure that the coupling agent is evenly dispersed in the system. Raise the reaction temperature to 75°C and react at this temperature for 3 hours. During the reaction, stirring was continued, and the stirring speed was adjusted to 500 rpm, so that the silane coupling agent and the nano-silica were fully reacted, and organic groups were grafted onto the surface of the nano-silica. After the reaction was completed, the reaction system was cooled to room temperature. Then, the sol after the reaction was ultrasonically treated using an ultrasonic disperser, with the ultrasonic power set to 400 W and the ultrasonic time set to 18 min. The dispersion state of the nano-silica particles was further refined by ultrasonic treatment, the stability of the sol was improved, and a stable nano-silica sol was finally formed.
[0049] Processing process of chopped glass fiber: Select vinyl trimethoxysilane, use anhydrous ethanol as solvent, prepare a dilute coupling agent solution with a mass fraction of 5%. During the preparation process, stir thoroughly to ensure that the coupling agent is completely dissolved in ethanol. Soak the chopped glass fiber (length 4mm) in the prepared dilute coupling agent solution to ensure that the glass fiber is completely immersed in the solution. The immersion time is controlled at 2h, so that the coupling agent molecules have enough time to react chemically with the surface of the glass fiber. After the immersion is completed, take the chopped glass fiber out of the coupling agent solution and gently absorb the excess solution on the surface with filter paper. Then, put the glass fiber into an oven for drying, the drying temperature is set to 90℃, and the drying time is 3h. Through the drying treatment, the solvent on the surface of the glass fiber is removed, and the coupling agent forms a stable chemical bond on the surface of the glass fiber, so that the active group that can be well combined with polyethylene succinate is formed on the surface of the glass fiber.
[0050] Example 1 The preparation method of poly(ethylene succinate) comprises the following steps: (1) Add succinic acid and ethylene glycol to a reactor, add a catalyst accounting for 0.5% of the total mass of the raw materials, control the reaction temperature at 180°C, the pressure at 0.3 MPa, the stirring speed at 300 rpm, react for 4 hours, and esterification reaction occurs to generate oligomers containing terminal carboxyl groups and terminal hydroxyl groups; then reduce the temperature to 150°C, add the treated nano-silica sol in batches under stirring conditions, increase the stirring speed to 500 rpm, and stir for 2 hours; (2) After the treatment in step (1) is completed, the reaction temperature is increased to 260°C, and the reaction system is evacuated to a vacuum pressure of 90 Pa. At the beginning of the polycondensation reaction, the organic montmorillonite is dispersed in toluene to form a suspension, which is added to the reaction system to continue the polycondensation reaction for 8 hours; (3) After the polycondensation reaction is completed, the product is taken out from the reactor and cooled to room temperature. The cooled product is blended and extruded with surface-treated short-cut glass fibers in a twin-screw extruder to obtain polyethylene succinate.
[0051] In the above, the molar ratio of succinic acid to ethylene glycol is 1:1.5; the addition amount of organic montmorillonite is 5% of the theoretical output mass of polyethylene succinate; the addition amount of glass fiber is 25% of the theoretical output mass of polyethylene succinate; and the addition amount of nano-silicon dioxide is 8% of the theoretical output mass of polyethylene succinate.
[0052] The method for preparing a catalyst comprises the following steps: a. Add mesoporous silica to an anhydrous ethanol solution containing KH-550, the amount of KH-550 is 3% of the mass of mesoporous silica, and stir the reaction at 80°C for 4h; b. In a dry glove box, tetrabutyl titanate was added to anhydrous ethanol to prepare a 0.1 mol / L tetrabutyl titanate ethanol solution; lanthanum acetate was added to anhydrous ethanol to prepare a 0.05 mol / L lanthanum acetate ethanol solution; zinc oxide nanoparticles and boric acid were taken, added to anhydrous ethanol, and ultrasonically dispersed for 60 min; c. The prepared tetrabutyl titanate ethanol solution and lanthanum acetate ethanol solution were mixed in a molar ratio of titanium: lanthanum = 3:1, stirred continuously during the mixing process, and polyvinyl pyrrolidone was added as a dispersant, stirred for 2h to obtain a main catalyst solution; then the mixed solution containing zinc oxide nanoparticles and boric acid was added to the main catalyst solution, and stirring was continued for 60min; d. The mesoporous silica obtained in step a is added to the solution obtained in step c, so that the catalyst is supported in the pores of the mesoporous silica, stirred at room temperature for 4 hours, and then heated and stirred at 80°C for 8 hours; e. The product obtained in step d was filtered and washed, then transferred to a vacuum drying oven and dried at 80°C for 24 hours; after drying, it was placed in a muffle furnace and calcined at 300°C for 3 hours while nitrogen protection was introduced for activation treatment to remove organic matter and impurities on the surface to obtain a catalyst; the catalyst specific surface area BET was 260m² / g.
[0053] The dosage of KH-550 is 3% of the mass of mesoporous silica, the dosage of zinc oxide nanoparticles is 10% of the total mass of the main catalyst, the dosage of boric acid is 5% of the total mass of the main catalyst; the dosage of polyvinyl pyrrolidone is 1% of the mass of tetrabutyl titanate ethanol solution; and the loading amount of the catalyst is 40%.
[0054] Example 2 The preparation method of poly(ethylene succinate) comprises the following steps: (1) Add succinic acid and ethylene glycol to a reactor, add a catalyst accounting for 0.3% of the total mass of the raw materials, control the reaction temperature at 170°C, the pressure at 0.2 MPa, the stirring speed at 200 rpm, and react for 3 hours to cause esterification reaction to generate oligomers containing terminal carboxyl groups and terminal hydroxyl groups; then reduce the temperature to 135°C, add the treated nano-silica sol in batches under stirring conditions, increase the stirring speed to 400 rpm, and stir for 2 hours; (2) After the treatment in step (1) is completed, the reaction temperature is raised to 240°C, and the reaction system is evacuated to a vacuum pressure of 80 Pa. At the beginning of the polycondensation reaction, the organic montmorillonite is dispersed in toluene to form a suspension, which is added to the reaction system to continue the polycondensation reaction for 5 hours; (3) After the polycondensation reaction is completed, the product is taken out from the reactor and cooled to room temperature. The cooled product is blended and extruded with surface-treated short-cut glass fibers in a twin-screw extruder to obtain polyethylene succinate.
[0055] In the above, the molar ratio of succinic acid to ethylene glycol is 1:1.3; the amount of organic montmorillonite added is 3% of the theoretical output mass of polyethylene succinate; the amount of glass fiber added is 20% of the theoretical output mass of polyethylene succinate; and the amount of nano-silicon dioxide added is 5% of the theoretical output mass of polyethylene succinate.
[0056] The method for preparing a catalyst comprises the following steps: a. Add mesoporous silica to an anhydrous ethanol solution containing KH-550, the amount of KH-550 is 2% of the mass of mesoporous silica, and stir the reaction at 70°C for 3h; b. In a dry glove box, tetrabutyl titanate was added to anhydrous ethanol to prepare a 0.1 mol / L tetrabutyl titanate ethanol solution; lanthanum acetate was added to anhydrous ethanol to prepare a 0.05 mol / L lanthanum acetate ethanol solution; zinc oxide nanoparticles and boric acid were taken, added to anhydrous ethanol, and ultrasonically dispersed for 30-60 min; c. The prepared tetrabutyl titanate ethanol solution and lanthanum acetate ethanol solution were mixed in a molar ratio of titanium: lanthanum = 3:1, stirred continuously during the mixing process, and polyvinyl pyrrolidone was added as a dispersant, stirred for 2h to obtain a main catalyst solution; then the mixed solution containing zinc oxide nanoparticles and boric acid was added to the main catalyst solution, and stirring was continued for 40min; d. The mesoporous silica obtained in step a is added to the solution obtained in step c, so that the catalyst is supported in the pores of the mesoporous silica, stirred at room temperature for 3 h, and then heated and stirred at 70 ° C for 6 h; e. The product obtained in step d was filtered and washed, then transferred to a vacuum drying oven and dried at 70°C for 20 h; after drying, it was placed in a muffle furnace and calcined at 280°C for 3 h while nitrogen protection was introduced for activation treatment to remove organic matter and impurities on the surface to obtain a catalyst; the catalyst specific surface area BET was 230 m² / g.
[0057] The dosage of KH-550 is 2% of the mass of mesoporous silica, the dosage of zinc oxide nanoparticles is 8% of the total mass of the main catalyst, the dosage of boric acid is 4% of the total mass of the main catalyst; the dosage of polyvinyl pyrrolidone is 0.8% of the mass of tetrabutyl titanate ethanol solution; and the loading amount of the catalyst is 30%.
[0058] Example 3 The preparation method of poly(ethylene succinate) comprises the following steps: (1) Add succinic acid and ethylene glycol to a reactor, add a catalyst accounting for 0.1% of the total mass of the raw materials, control the reaction temperature at 160°C, the pressure at 0.1 MPa, the stirring speed at 100 rpm, react for 2 hours, and esterification reaction occurs to generate oligomers containing terminal carboxyl groups and terminal hydroxyl groups; then reduce the temperature to 120°C, add the treated nano-silica sol in batches under stirring conditions, increase the stirring speed to 300 rpm, and stir for 1 hour; (2) After the treatment in step (1) is completed, the reaction temperature is increased to 220°C, and the reaction system is evacuated to a vacuum pressure of 80 Pa. At the beginning of the polycondensation reaction, the organic montmorillonite is dispersed in toluene to form a suspension, which is added to the reaction system to continue the polycondensation reaction for 3 hours; (3) After the polycondensation reaction is completed, the product is taken out from the reactor and cooled to room temperature. The cooled product is blended and extruded with surface-treated short-cut glass fibers in a twin-screw extruder to obtain polyethylene succinate.
[0059] In the above, the molar ratio of succinic acid to ethylene glycol is 1:1.2; the amount of organic montmorillonite added is 2% of the theoretical output mass of polyethylene succinate; the amount of glass fiber added is 10% of the theoretical output mass of polyethylene succinate; and the amount of nano-silicon dioxide added is 3% of the theoretical output mass of polyethylene succinate.
[0060] The method for preparing a catalyst comprises the following steps: a. Add mesoporous silica to an anhydrous ethanol solution containing KH-550, the amount of KH-550 is 1% of the mass of mesoporous silica, and stir the reaction at 60°C for 2h; b. In a dry glove box, tetrabutyl titanate was added to anhydrous ethanol to prepare a 0.1 mol / L tetrabutyl titanate ethanol solution; lanthanum acetate was added to anhydrous ethanol to prepare a 0.05 mol / L lanthanum acetate ethanol solution; zinc oxide nanoparticles and boric acid were taken, added to anhydrous ethanol, and ultrasonically dispersed for 30 min; c. The prepared tetrabutyl titanate ethanol solution and lanthanum acetate ethanol solution were mixed in a molar ratio of titanium: lanthanum = 3:1, stirred continuously during the mixing process, and polyvinyl pyrrolidone was added as a dispersant, stirred for 1 hour to obtain a main catalyst solution; then the mixed solution containing zinc oxide nanoparticles and boric acid was added to the main catalyst solution, and stirring was continued for 30 minutes; d. The mesoporous silica obtained in step a is added to the solution obtained in step c, so that the catalyst is supported in the pores of the mesoporous silica, stirred at room temperature for 2 h, and then heated and stirred at 60 ° C for 4 h; e. The product obtained in step d was filtered, washed, transferred to a vacuum drying oven, and dried at 60°C for 12 hours; after drying, placed in a muffle furnace, calcined at 250°C for 2 hours, and nitrogen was introduced for protection, and activation treatment was performed to remove organic matter and impurities on the surface to obtain a catalyst; the catalyst specific surface area BET was 210m² / g.
[0061] The dosage of KH-550 is 1% of the mass of mesoporous silica, the dosage of zinc oxide nanoparticles is 5% of the total mass of the main catalyst, the dosage of boric acid is 2% of the total mass of the main catalyst; the dosage of polyvinyl pyrrolidone is 0.5% of the mass of tetrabutyl titanate ethanol solution; and the loading amount of the catalyst is 20%.
[0062] Comparative Example 1 Compared with Example 1, no KH-550 was added during the catalyst preparation.
[0063] Comparative Example 2 Compared with Example 1, no mesoporous silica was added during the catalyst preparation, ie, no loading was performed.
[0064] Comparative Example 3 Compared with Example 1, no zinc oxide nanoparticles were added during the catalyst preparation.
[0065] Comparative Example 4 Compared with Example 1, no boric acid was added during the catalyst preparation.
[0066] Comparative Example 5 Compared with Example 1, no polyvinyl pyrrolidone was added during the preparation of the catalyst.
[0067] Comparative Example 6 Compared with Example 1, no nano silicon dioxide was added.
[0068] Comparative Example 7 Compared with Example 2, no organic montmorillonite was added.
[0069] Comparative Example 8 Compared with Example 3, no glass fiber was added.
[0070] The test data of the catalysts prepared in Examples 1-3 and Comparative Examples 1-5 are shown in Table 1.
[0071] The test data of the polyethylene succinate prepared in Examples 1-3 and Comparative Examples 6-8 are shown in Table 2.
[0072] Table 1: Test data of the catalysts prepared in Examples 1-3 and Comparative Examples 1-5
[0073]
[0074] It can be seen from Table 1 that the catalysts of Examples 1-3 have high activity (short esterification time, fast acid value drop, high polycondensation intrinsic viscosity), good selectivity (by-products <2%), excellent thermal / chemical stability (activity drop ≤14%), firm loading (shedding rate ≤4%) and good reusability (intrinsic viscosity change ≤9%). When the loading amount is 30%, the carrier and the active component are more evenly distributed, and the catalytic efficiency is the highest. The comparison shows that the mesoporous silica carrier (Comparative Example 2), KH-550 (Comparative Example 1), and zinc oxide / boric acid (Comparative Examples 3-4) are crucial to improving the catalytic performance.
[0075] Table 2: Test data of polyethylene succinate obtained in Examples 1-3 and Comparative Examples 6-8
[0076]
[0077] As can be seen from Table 2, the thermal stability (initial decomposition temperature ≥ 280°C), mechanical properties (tensile strength ≥ 45MPa), barrier properties (oxygen permeability ≤ 5.0) and degradability (mass loss rate ≥ 30%) of the polyethylene succinate of Examples 1-3 are significantly better than those of Comparative Examples 6-8. The synergistic effect of organic montmorillonite, glass fiber and nano-silica (performance decreased when no addition was made in Comparative Examples 6-8) is the key, indicating that the three together improve the comprehensive performance of the material.
[0078] Application Example 1 Polyethylene succinate is used to prepare water quality monitoring buoys.
[0079] The preparation method of the carbon nanotube suspension is as follows: placing the carbon nanotubes in a mixed acid solution of concentrated nitric acid and concentrated sulfuric acid, and reflux treatment at 80°C for 4 hours; washing with deionized water until neutral, and drying to obtain purified carboxylated carbon nanotubes; dissolving polyvinyl alcohol in deionized water to prepare a solution with a mass fraction of 5%; adding the purified carbon nanotubes to the polyvinyl alcohol solution, and ultrasonically treating (power 500W, time 60min) to uniformly coat the surface of the carbon nanotubes with PVA; centrifugation and drying to obtain PVA-coated carbon nanotubes; adding the dried PVA-coated carbon nanotubes to N,N-dimethylformamide (DMF), and ultrasonically dispersing for 1 hour to form a uniform suspension.
[0080] The preparation method of nano calcium carbonate dispersion is: surface modification of nano calcium carbonate is carried out with fatty acid and titanate coupling agent, and KH-550 is added at the same time, and stirred at 120°C for 2 hours to make its surface organic; the preparation method of graphene dispersion is: graphene is made into a uniform dispersion in water by ultrasonic exfoliation. The addition amount of KH-550 is 5% of the mass of nano calcium carbonate.
[0081] The preparation method of the water quality monitoring buoy comprises the following steps: Ⅰ. In a high-speed mixer, first add polyethylene succinate particles, then add hindered amine light stabilizer, maleic anhydride grafted polyethylene succinate in sequence, and stir at 80°C for 10 minutes; then add nano-silver antibacterial agent, continue stirring, then add nano-calcium carbonate and graphene dispersion, and continue stirring for 20 minutes; Ⅱ. Add the material obtained in step Ⅰ into a twin-screw extruder for melt blending and extrusion. At the same time, during the extrusion process, add the carbon nanotube suspension into the twin-screw extruder and mix it with other materials. Control the screw speed at 300 rpm. Then extrude it into the shape of a water quality monitoring buoy through a mold, and then cool it down by air cooling or water cooling to obtain a water quality monitoring buoy.
[0082] The weight proportions of the raw materials are as follows: polyethylene succinate: 100 parts; carbon nanotubes: 3 parts; hindered amine light stabilizer: 2 parts; nano silver antibacterial agent: 1 part; graphene: 2 parts; maleic anhydride grafted polyethylene succinate: 15 parts; and nano calcium carbonate: 15 parts.
[0083] Application Example 2 Polyethylene succinate is used to prepare water quality monitoring buoys.
[0084] The preparation method of the carbon nanotube suspension is as follows: placing the carbon nanotubes in a mixed acid solution of concentrated nitric acid and concentrated sulfuric acid, and reflux treatment at 70°C for 3 hours; washing with deionized water until neutral, and drying to obtain purified carboxylated carbon nanotubes; dissolving PVA in deionized water to prepare a solution with a mass fraction of 3%; adding the purified carbon nanotubes to the PVA solution, and ultrasonically treating (power 300W, time 40min) to uniformly coat the PVA on the surface of the carbon nanotubes; centrifugation and drying to obtain PVA-coated carbon nanotubes; adding the dried PVA-coated carbon nanotubes to N,N-dimethylformamide, and ultrasonically dispersing for 2 hours to form a uniform suspension.
[0085] The preparation method of nano calcium carbonate dispersion is: surface modification of nano calcium carbonate is carried out with fatty acid and titanate coupling agent, and KH-550 is added at the same time, and stirred at 100°C for 2 hours to make its surface organic; the preparation method of graphene dispersion is: graphene is made into a uniform dispersion in anhydrous ethanol by ultrasonic exfoliation. The addition amount of KH-550 is 3% of the mass of nano calcium carbonate.
[0086] The preparation method of the water quality monitoring buoy comprises the following steps: Ⅰ. In a high-speed mixer, first add polyethylene succinate particles, then add hindered amine light stabilizer, maleic anhydride grafted polyethylene succinate in sequence, and stir at 70°C for 8 minutes; then add nano-silver antibacterial agent, continue stirring, then add nano-calcium carbonate and graphene dispersion, and continue stirring for 15 minutes; Ⅱ. Add the material obtained in step Ⅰ into a twin-screw extruder for melt blending and extrusion. At the same time, during the extrusion process, add the carbon nanotube suspension into the twin-screw extruder and mix it with other materials. Control the screw speed at 200 rpm. Then extrude it into the shape of a water quality monitoring buoy through a mold, and then cool it down by air cooling or water cooling to obtain a water quality monitoring buoy.
[0087] The mass parts of each raw material are: polyethylene succinate: 100 parts; carbon nanotubes: 2 parts; hindered amine light stabilizer: 1 part; nano silver antibacterial agent: 0.8 parts; graphene: 1 part; maleic anhydride grafted polyethylene succinate: 10 parts; nano calcium carbonate: 10 parts.
[0088] Application Example 3 Polyethylene succinate is used to prepare water quality monitoring buoys.
[0089] The preparation method of the carbon nanotube suspension is as follows: placing the carbon nanotubes in a mixed acid solution of concentrated nitric acid and concentrated sulfuric acid, and reflux treatment at 60°C for 2 hours; washing with deionized water until neutral, and drying to obtain purified carboxylated carbon nanotubes; dissolving polyvinyl alcohol in deionized water to prepare a solution with a mass fraction of 1%; adding the purified carbon nanotubes to the PVA solution, ultrasonic treatment (power 200W, time 30min), so that PVA is evenly coated on the surface of the carbon nanotubes; centrifugal separation and drying to obtain PVA-coated carbon nanotubes; adding the dried PVA-coated carbon nanotubes to N,N-dimethylformamide, mechanically stirring (speed 1000 rpm, time 2h), to form a uniform suspension.
[0090] The preparation method of nano calcium carbonate dispersion is: surface modification of nano calcium carbonate is carried out with fatty acid and titanate coupling agent, and KH-550 is added at the same time, and stirred at 80°C for 1 hour to make its surface organic; the preparation method of graphene dispersion is: graphene is made into a uniform dispersion in anhydrous ethanol by ultrasonic exfoliation. The addition amount of KH-550 is 1% of the mass of nano calcium carbonate.
[0091] The preparation method of the water quality monitoring buoy comprises the following steps: Ⅰ. In a high-speed mixer, first add polyethylene succinate particles, then add hindered amine light stabilizer, maleic anhydride grafted polyethylene succinate in sequence, and stir at 50°C for 5 minutes; then add nano-silver antibacterial agent, continue stirring, then add nano-calcium carbonate and graphene dispersion, and continue stirring for 10 minutes; Ⅱ. Add the material obtained in step Ⅰ into a twin-screw extruder for melt blending and extrusion. At the same time, during the extrusion process, add the carbon nanotube suspension into the twin-screw extruder and mix it with other materials. Control the screw speed at 100 rpm. Then extrude it into the shape of a water quality monitoring buoy through a mold, and then cool it down by air cooling or water cooling to obtain a water quality monitoring buoy.
[0092] The mass parts of each raw material are: polyethylene succinate: 100 parts; carbon nanotubes: 1 part; hindered amine light stabilizer: 0.5 parts; nano silver antibacterial agent: 0.3 parts; graphene: 0.5 parts; maleic anhydride grafted polyethylene succinate: 5 parts; nano calcium carbonate: 5 parts.
[0093] Comparative Example 1 was applied, and the polyethylene succinate prepared in Comparative Example 1 was used to take the middle value.
[0094] Compared with Application Example 1, Application Comparative Example 2 does not add nano-silicon dioxide and graphene.
[0095] In application comparative example 3, compared with application example 1, no carbon nanotubes are added, and the amount of nano-calcium carbonate added is the sum of the masses of nano-calcium carbonate and carbon nanotubes in example 1.
[0096] Compared with Application Example 1, Application Comparative Example 4 does not add nano silicon dioxide.
[0097] Compared with Application Example 1, Application Comparative Example 5 did not pretreat the nanomaterial.
[0098] The test data of application examples 1-3 and application comparative examples 1-5 are shown in Table 3.
[0099] Table 3: Test data of application examples 1-3 and application comparative examples 1-5
[0100]
[0101] It can be seen from Table 3 that the thermal stability (initial decomposition temperature ≥ 305°C), mechanical strength (tensile strength ≥ 60MPa), antibacterial rate (≥ 94%) and electrical properties (volume resistivity ≥ 1.4×10¹³Ω·m) of the water quality monitoring buoys using Examples 1-3 are better than those of the comparative examples. Nanomaterial pretreatment (performance degradation in comparative example 5) and component synergy (performance degradation when no key components were added to comparative examples 2-4) verify the necessity of the formulation design of this application, ensuring the durability and functionality of the buoy in complex environments.
[0102] The present invention significantly improves the thermal stability, mechanical properties and degradability of polyethylene succinate by optimizing the catalyst (high activity and high stability) and the material formulation (synergistic enhancement of organic montmorillonite / glass fiber / nano-silica), and gives the water quality monitoring buoy excellent comprehensive performance (weather resistance, antibacterial, and high barrier), thus possessing significant technical advantages.
Claims
1. A method for preparing polyethylene succinate, characterized in that: The following steps are involved: (1) Add succinic acid and ethylene glycol to a reactor, add a catalyst accounting for 0.1-0.5% of the total mass of the raw materials, control the reaction temperature at 160-180°C, the pressure at 0.1-0.3 MPa, the stirring speed at 100-300 rpm, react for 2-4 hours, and esterification reaction occurs to generate oligomers containing terminal carboxyl groups and terminal hydroxyl groups; then reduce the temperature to 120-150°C, add nano-silica sol in batches under stirring conditions, increase the stirring speed to 300-500 rpm, and stir for 1-2 hours; (2) After the treatment in step (1) is completed, the reaction temperature is increased to 220-260°C, and the reaction system is evacuated to a vacuum with a pressure lower than 100 Pa. At the beginning of the polycondensation reaction, the organic montmorillonite is dispersed in toluene to form a suspension, which is added to the reaction system to continue the polycondensation reaction for 3-8 hours; (3) After the polycondensation reaction is completed, the product is taken out from the reactor and cooled to room temperature. The cooled product is blended and extruded with short-cut glass fibers in a twin-screw extruder to obtain polyethylene succinate.
2. The method for preparing poly(ethylene succinate) according to claim 1, characterized in that: The molar ratio of succinic acid to ethylene glycol is 1:(1.2-1.5); the addition amount of organic montmorillonite is 2-5% of the theoretical output mass of polyethylene succinate; the addition amount of glass fiber is 10-25% of the theoretical output mass of polyethylene succinate; and the addition amount of nano-silicon dioxide is 3-8% of the theoretical output mass of polyethylene succinate.
3. The method for preparing poly(ethylene succinate) according to claim 1, characterized in that: The nano-silica sol must be pretreated before being added, and the pretreatment process is as follows: dispersing the nano-silica in anhydrous ethanol, adding a silane coupling agent, and stirring at 70-80°C for 2-3 hours to graft organic groups on the surface of the nano-silica to form a stable sol; and the chopped glass fibers must be pretreated before being added, and the pretreatment process is as follows: soaking the chopped glass fibers in a solution of vinyl trimethoxysilane, taking them out after 1-2 hours, and drying them.
4. The method for preparing poly(ethylene succinate) according to claim 1, characterized in that: The method for preparing the catalyst comprises the following steps: a. Add mesoporous silica to an anhydrous ethanol solution containing a silane coupling agent, the amount of the silane coupling agent being 1-3% of the mass of the mesoporous silica, and stir the reaction at 60-80°C for 2-4h; b. In a dry glove box, tetrabutyl titanate was added to anhydrous ethanol to prepare a 0.1 mol / L tetrabutyl titanate ethanol solution; lanthanum acetate was added to anhydrous ethanol to prepare a 0.05 mol / L lanthanum acetate ethanol solution; zinc oxide nanoparticles and boric acid were taken, added to anhydrous ethanol, and ultrasonically dispersed for 30-60 min; c. The prepared tetrabutyl titanate ethanol solution and lanthanum acetate ethanol solution were mixed in a molar ratio of titanium: lanthanum = 3:1, and stirred continuously during the mixing process, and polyvinyl pyrrolidone was added as a dispersant, and stirred for 1-2h to obtain a main catalyst solution; then the mixed solution containing zinc oxide nanoparticles and boric acid was added to the main catalyst solution, and stirring was continued for 30-60min; d. The mesoporous silica obtained in step a is added to the solution obtained in step c, so that the catalyst is loaded in the pores of the mesoporous silica, stirred at room temperature for 2-4 hours, and then heated and stirred at 60-80°C for 4-8 hours; e. The product obtained in step d is filtered and washed, then transferred to a vacuum drying oven and dried at 60-80°C for 12-24h; after drying, it is placed in a muffle furnace and calcined at 250-300°C for 2-3h while nitrogen is introduced for protection, and an activation treatment is performed to remove organic matter and impurities on the surface to obtain a catalyst; the catalyst specific surface area BET ≥ 200m² / g.
5. The method for preparing polyethylene succinate according to claim 4, characterized in that: The amount of the silane coupling agent is 1-3% of the mass of the mesoporous silica, the amount of the zinc oxide nanoparticles is 5-10% of the total mass of the main catalyst, the amount of boric acid is 2-5% of the total mass of the main catalyst; the amount of polyvinyl pyrrolidone is 0.5-1% of the mass of the tetrabutyl titanate ethanol solution; and the loading amount of the catalyst is 20-40%.
6. A polyethylene succinate, characterized in that: The poly(ethylene succinate) is prepared by the preparation method of any one of claims 1 to 5.
7. Use of the polyethylene succinate according to claim 6, characterized in that: Used to prepare water quality monitoring buoys.
8. The use of polyethylene succinate according to claim 7, characterized in that: The method for preparing the water quality monitoring buoy comprises the following steps: Ⅰ. In a high-speed mixer, first add polyethylene succinate particles, then add hindered amine light stabilizer, maleic anhydride grafted polyethylene succinate in sequence, and stir at 50-80°C for 5-10 minutes; then add nano-silver antibacterial agent, continue stirring, then add nano-calcium carbonate and graphene dispersion, and continue stirring for 10-20 minutes; Ⅱ. Add the material obtained in step Ⅰ into a twin-screw extruder for melt blending and extrusion. At the same time, During the extrusion process, the carbon nanotube suspension is added to the twin-screw extruder, mixed with other materials, and the screw speed is controlled at 100-300 rpm; it is then extruded through a mold into the shape of a water quality monitoring buoy, and then cooled and shaped by air cooling or water cooling to obtain a water quality monitoring buoy.
9. The use of polyethylene succinate according to claim 8, characterized in that: The weight proportions of the raw materials are as follows: polyethylene glycol succinate: 100 parts; carbon nanotubes: 1-3 parts; hindered amine light stabilizer: 0.5-2 parts; nano silver antibacterial agent: 0.3-1 parts; Graphene: 0.5-2 parts; Maleic anhydride grafted polyethylene succinate: 5-15 parts; Nano calcium carbonate: 5-15 parts.
10. The use of polyethylene succinate according to claim 8, characterized in that: The preparation method of the carbon nanotube suspension is as follows: placing the carbon nanotube in a mixed acid solution of concentrated nitric acid and concentrated sulfuric acid, reflux treatment at 60-80°C for 2-4h, then washing with deionized water until neutral, and drying to obtain carboxylated carbon nanotubes; dissolving polyvinyl alcohol in deionized water to prepare a solution with a mass fraction of 1-5%, adding the carboxylated carbon nanotubes therein, ultrasonic treatment, centrifugal separation and drying to obtain polyvinyl alcohol-coated carbon nanotubes; then adding the carbon nanotubes to N,N-dimethylformamide, ultrasonic dispersion or mechanical stirring to form a suspension; the preparation method of the nano calcium carbonate dispersion is as follows: surface modification treatment of the nano calcium carbonate is performed with fatty acid and titanate coupling agent, and silane coupling agent is added at the same time, stirring at 80-120°C for 1-2h to make its surface organic; the preparation method of the graphene dispersion is as follows: preparing a uniform dispersion of graphene in an organic solvent or water by ultrasonic stripping.
Citation Information
Patent Citations
Preparation method for aliphatic polyester / phyllosilicate nano-composite material
CN101343405A
Fully-degradable polyester / inorganic nanoparticle composite material and method for preparing same
CN101838447A
Preparation method of polyethylene glycol succinate
CN116925331A